The Development of Flipped Classroom Learning Model to Improve Students’ HOTS in Covid 19 Pandemic Era - Syamsidah, Syamsidah; Jusniar, Jusniar; T., Ratnawati; Muhiddin, Amir (Universitas Negeri Makassar, 2022)
Abstract. The study aims to identify the stages of development of Flipped Classroom (FC) model, which can improve students’ HOTS and the validity and practicality of the model. The research subjects were all 10th-grade students following the Crafts and Entrepreneurship subject and the subject's teacher. Data were collected through Focus Group Discussion (FGD), interviews, questionnaire, checklist, and scale and analyzed descriptively. The research findings show that the Crafts and Entrepreneurship subject was taught with conventional method which more dominantly involved teacher rather than students from defining stage like front end analysis, students’ analysis, task analysis, and learning goal specification analysis. The stages show that students’ ability was low, including receiving the learning material and doing the final task, which further implied their HOTS. However, their academic skill was probably relatively good. Then, the review showed that learning media was valid, effective, and practical. The findings were categorized as valid since experts performed the validation, and the trial results show a validity level of 3.16. This study found that the learning material for the FC model was practical. The practical material was developed by implementing the input we obtained from the trial using a questionnaire to gather data about the perception of three Crafts and Entrepreneurship subject teachers and 33 students following the subject using the FC learning model and media.